Aging effects on the liver aldolase of rabbits (Short Communication) - Anderson, Peter J. (1974)
A chemical method is used to determine the amount of aldolase sequence in rabbit livers. It is demonstrated that the aldolase sequences of the livers of young rabbits are more efficient catalytically than are those from the livers of old rabbits. The presence of altered residues in the aldolase sequences of old animals may account for these observations.